FOXM1 mediates resistance to docetaxel in gastric cancer via up‐regulating Stathmin. Issue 5 (14th March 2014) - Li, Xiaoxiao; Yao, Ruyong; Yue, Lu; Qiu, Wensheng; Qi, Weiwei; Liu, Shihai; Yao, Yasai; Liang, Jun
Abstract Docetaxel is commonly used as an effective chemotherapeutic drug for gastric cancer patients recently. With the increasing emergence of docetaxel resistance nowadays, identification of suitable biomarkers for predicting chemosensitivity to docetaxel may be a key role for improving therapeutic effects for gastric cancer patients. In this study, we investigated the correlation between the expression of transcription factor forkhead box protein M1 (FOXM1) and chemotherapy response to docetaxel in gastric cancer, the possible mechanism for which was further explored. As a result, FOXM1 overexpression was shown to mediate resistance to docetaxel in gastric cancers. It altered microtubule dynamics to protect tumour cells from docetaxel‐induced apoptosis. Mechanistic investigations revealed that tubulin‐destabilizing protein Stathmin, which mediated docetaxel resistance in FOXM1‐silenced gastric cancer cells, is a direct down‐stream target of FOXM1, whereas another microtubule dynamics protein mitotic centromere–associated kinesin (MCAK), shown to be related to docetaxel resistance in gastric cancer cells, is not associated with FOXM1 expression significantly. These results were further provided by immunohistochemical analysis, indicating that FOXM1 and Stathmin expression levels were correlated in 103 post‐operational gastric cancer specimens. Moreover, when we attenuated FOXM1 expression with FOXM1 inhibitor thiostrepton, docetaxel resistance in gastric cancers was found to be reversed, simultaneously with the down‐regulation of FOXM1 and Stathmin. Therefore, FOXM1 can be a useful marker for predicting and monitoring docetaxel response. Through the inhibition of FOXM1, docetaxel resistance can be reversed, and thus FOXM1 could be a new therapeutic target in docetaxel‐resistant gastric cancer.